Can the technological mediation approach improve technology assessment? A critical view from 'within'*. Issue 3 (2nd September 2018) - de Boer, Bas; Hoek, Jonne; Kudina, Olga
ABSTRACT: The technological mediation approach aspires to complement current Technology Assessment (TA) practices. It aims to do so by addressing ethical concerns from 'within' human-technology relations leading to ethical Constructive Technology Assessment (eCTA), as articulated by Kiran, Asle H., Nelly Oudshoorn, and Peter-Paul Verbeek in their 2015 article. In this paper, we problematize this ambition. Firstly, we situate the technological mediation approach in the history of TA. Secondly, as a study into the normativity from 'within' human-technology relations, we reveal the phenomenological and existential origins of Verbeek's technological mediation approach. Thirdly, we show that there are two possible readings of this approach: a strong and a weak one. The weak reading can augment current TA practices but is eventually uncommitted to the idea of technological mediation. The strong reading defines a wholly new scope for our engagement with (emerging) technologies but is incompatible with existing TA approaches.